Social, Environmental and Biological Determinants of Cerebral Palsy in Children with Intellectual Disabilities (ID) in India - Lakhan, R (Nepal Journal of Epidemiology, 2013)
Background Cerebral palsy (CP) is a global public health problem affecting 2.12 to 2.45 per 1000 live birth across the world. Cerebral palsy is an upper motor neuron, non-progressive disorder commonly associated with intellectual disability. The presence of cerebral palsy effects person’s overall life. Objectives This study primarily sought predictive capacity of social, environmental and biological determinants of CP in ID. Materials and Methods This is a cross-sectional study design. A total of 262 children, aged 3 to 18 years, with ID were assessed for cerebral palsy and diagnosed on basis of clinical examination in a community based rehabilitation project in Barwani, India. Information was collected by parent interviews, on social, environmental and biological determinants. A logistic regression model has been applied between determinants and CP. Results Logistic regression demonstrated that likelihood of CP in ID children can be predicted on bases of their age (odd ratio = 0.856, CI 95% - 0.76-0.95), intelligence quotients (IQ) (odd ratio = 0.782, CI 95% - 0.73-0.83) and family history of intellectual disabilities (odd ratio = 0.051, CI 95% - 2.36 -0.99) and epilepsy (odd ratio = 0.008, CI 95% - 2.58-1.28). Comorbid conditions of downs syndrome and epilepsy also predicts likelihood of CP in ID. Conclusion Likelihood of CP in ID children can be predicted by their age, IQ, family history of intellectual disability, epilepsy and comorbid conditions of downs syndrome and epilepsy. Gender, socio-economic status and population (tribal versus non-tribal) determinants have no predictive relation with CP in the group. DOI: http://dx.doi.org/10.3126/nje.v3i3.9187 Nepal Journal of Epidemiology 2013;3(3): 262-268